The Roberts Court and Police Practices: The Impact of Chief Justice Roberts and Justice Alito in Police Practices Cases - Call, Jack E. (American journal of criminal justice, 2010)
In police practices cases, the Supreme Court decides issues that determine when the law enforcement interest in solving crimes must give way to the interest of individuals to be left alone by the government. The replacement of Chief Justice Rehnquist with John Roberts and Justice Sandra Day O’Connor with Samuel Alito has now been in place for more than four terms. The time is appropriate to assess the likely impact of these two new members of the Court on police practices cases. This article examines that question by analyzing both the police practices opinions written by Roberts and Alito while they served on U.S. Courts of Appeals and their opinions while on the Supreme Court through the 2008-09 term. The conclusion is that the previous pattern of the police prevailing in the vast majority of these cases is unlikely to change. In addition, there is some evidence to suggest that Chief Justice Roberts is aligning himself closely with Justice Scalia in these cases and may be setting the stage for a significant modification or even elimination of the exclusionary rule.